A Century‐Long Trajectory of Phosphorus Loading and Export From Mississippi River Basin to the Gulf of Mexico: Contributions of Multiple Environmental Changes. Issue 6 (7th June 2022) - Bian, Zihao; Pan, Shufen; Wang, Zhuonan; Yao, Yuanzhi; Xu, Rongting; Shi, Hao; Kalin, Latif; Anderson, Christopher; Justic, Dubravko; Lohrenz, Steven; Tian, Hanqin
Abstract: Phosphorus (P) control is critical to mitigating eutrophication in aquatic ecosystems, but the effectiveness of controlling P export from soils has been limited by our poor understanding of P dynamics along the land‐ocean aquatic continuum as well as the lack of well‐developed process models that effectively couple terrestrial and aquatic biogeochemical P processes. Here, we coupled riverine P biogeochemical processes and water transport with terrestrial processes within the framework of the Dynamic Land Ecosystem Model to assess how multiple environmental changes, including fertilizer and manure P uses, land use, climate, and atmospheric CO2, have affected the long‐term dynamics of P loading and export from the Mississippi River Basin to the Gulf of Mexico during 1901–2018. Simulations show that riverine exports of dissolved inorganic phosphorus (DIP), dissolved organic phosphorus, particulate organic phosphorus (POP), and particulate inorganic phosphorus (PIP) increased by 42%, 53%, 60%, and 53%, respectively, since the 1960s. Riverine DIP and PIP exports were the dominant components of the total P flux. DIP export was mainly enhanced by the growing mineral P fertilizer use in croplands, while increased PIP and POP exports were a result of the intensified soil erosion due to increased precipitation. Climate variability resulted in substantial interannual and decadal variations in P loading and export. Soil legacy P continues to contribute to P loading. Our findings highlight the necessity to adopt effective P management strategies to control P losses through reductions in soil erosion, and additionally, to improve P use efficiency in crop production. Plain Language Summary: Phosphorus enrichment in aquatic systems is one of the critical reasons for water quality degradation. Terrestrial ecosystems have received large amounts of phosphorus inputs and are a major phosphorus source for water bodies. Linking the phosphorus cycles in both terrestrial and aquatic ecosystems is helpful for understanding phosphorus flux from land to ocean. In this study, we simulated phosphorus processes in both terrestrial and aquatic systems and estimated phosphorus exports from the Mississippi River Basin to the Gulf of Mexico during 1901–2018. The simulated results show that riverine phosphorus exports have increased since the 1960s. The increasing usage of fertilizer and manure in agricultural activities as well as intensified erosion due to increasing extreme precipitation could be the major causes for the increasing riverine phosphorus export. This study provides insight into the mechanisms mediating riverine phosphorus exports over the past century in the context of global change. Key Points: An aquatic phosphorus module was incorporated into a land biosphere model to investigate phosphorus dynamics along the land‐ocean continuum Simulated riverine exports of dissolved inorganic phosphorus, dissolved organic phosphorus, particulate inorganic phosphorus, and particulate organic phosphorus from the Mississippi River Basin increased remarkably during 1901–2018 The growing use of fertilizer and intensified soil erosion were the primary reasons for the increasing phosphorus exports